2017
DOI: 10.3390/geriatrics2030019
|View full text |Cite
|
Sign up to set email alerts
|

Risk Prediction Models for Post-Stroke Dementia

Abstract: A strong association exists between stroke and dementia with both diseases linked to ageing. Survival rates from stroke are improving which would equate to an ever-expanding population of patients at risk of future dementia. Early or timelier identification of dementia has become a priority in many countries, including the UK. Although screening for dementia is not advocated, targeting at risk populations could be used to reduce an individual's risk via intervention (i.e., personalised medicine), where availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…In this analysis we used data collected between 1995 and 2018. The methods of the SLSR have been described in detail by Wolfe et al [6][7][8][9][10][11][12][13][14][15][16][17] and are summarised here. All patients with a first ever stroke after 1 st January 1995 and residing in a defined inner-city area of South London were eligible for inclusion.…”
Section: Source Of Datamentioning
confidence: 99%
See 2 more Smart Citations
“…In this analysis we used data collected between 1995 and 2018. The methods of the SLSR have been described in detail by Wolfe et al [6][7][8][9][10][11][12][13][14][15][16][17] and are summarised here. All patients with a first ever stroke after 1 st January 1995 and residing in a defined inner-city area of South London were eligible for inclusion.…”
Section: Source Of Datamentioning
confidence: 99%
“…Whilst these models could be a useful assistive tool to predict cognitive decline, atrophy are not systematically measured in the practice. Tang et al [11] reported that several models have been developed for people with stroke to predict dementia [12] [13] or cognitive impairment [14] [15] and their predictive accuracy was found to be acceptable. Different variables including demographic, cognitive test scores and neuroimaging markers have been incorporated into different models, with predictive accuracy found to be moderate to high.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study sample, 62.5% of residents were female and over 80% of residents were 75 years of age or older, with those aged 85 years and older forming the biggest age group of residents. The prevalence of cognitive impairment post-stroke upon admission to nursing homes is an area in which there is a dearth of research, yet it may have considerable implications for health service planners, as the demand for nursing home placement for those with PSCI is likely to increase in the coming decades in line with population ageing [22][23][24].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The extent of the utilisation of nursing home care both for those with cognitive impairment and for those with dementia post-stroke has yet to be determined. These data are important for health service planners and policy makers, as epidemiological evidence suggests that, as the risks of stroke and cognitive impairment increase exponentially with age, PSCI is likely to become more prevalent in the coming decades, in line with an ageing population [22][23][24]. This is likely to have considerable implications for the demand for nursing home care places to meet this growing demand.…”
Section: Introductionmentioning
confidence: 99%